Synergy between autotrophic denitrification and Anammox driven by FeS in a fluidized bed bioreactor for advanced nitrogen removal. (October 2021) - Ma, Jingde; Wei, Jingyue; Kong, Qiaoping; Li, Zemin; Pan, Jianxin; Chen, Ben; Qiu, Guanglei; Wu, Haizhen; Zhu, Shuang; Wei, Chaohai
Abstract: On the basis of the metabolic synergy between autotrophic denitrification (AuDen) and anaerobic ammonium oxidation (Anammox), the feasibility of a novel ferrous sulfide (FeS)-driven AuDen and Anammox coupled system (FS-DADAS) was investigated. The nitrogen removal performance of FS-DADAS was investigated in a lab-scale fluidized bed bioreactor fed with synthetic wastewater containing NH4 + -N and NO3 − -N. The results of long-term operation (120 days) demonstrated the promising performance of the system with 100% NO3 − -N removal and NH4 + -N concentrations lower than 8.11 mg L −1 in the effluent at a nitrogen loading rate of 0.20 g-N·(L·d) −1 . Sufficient NO2 − -N was provided by the AuDen for Anammox where a high removal rate of total nitrogen (TN) was achieved. The contribution of Anammox to TN removal was at >80%. The reactor could maintain a stable pH with less SO4 2− production owing to the fact that Fe(II) and S acted as electron donors. FeS gradually transformed into a sheet-like secondary mineral, FeOOH. AuDen ( Thiobacillus ) and Anammox bacteria ( Candidatus Kuenenia) were successfully retained in the bioreactor, with relative abundance values of 18.82%–23.64% and 3.52%–8.67%, respectively. FS-DADAS is a promising technology for the complete removal of TN from wastewaters with low C/N ratios at low energy consumption. Graphical abstract: Image 1 Highlights: A novel total nitrogen removal system named "FS-DADAS" is proposed. FS-DADAS is a combination of AuDen and Anammox with FeS as the electron donor. Autotrophic denitrification and Anammox bacteria achieved functional combinations. Fluidized bed reactor with FS-DADAS exhibited mass transfer and separation function.